Clinical efficacy and safety of tripterygium wilfordii glycosides in the treatment of idiopathic membranous nephropathy: a systematic review and meta-analysis - Liu, Ying; Lu, Keda (Frontiers in Pharmacology, 2025)
BackgroundIdiopathic membranous nephropathy (IMN) is a common cause of nephrotic syndrome in adults, with current immunosuppressive therapies often limited by incomplete efficacy, significant toxicity, and high cost. Extracts from Tripterygium wilfordii, particularly its glycosides (TWG), have emerged as a potential alternative with immunomodulatory properties.ObjectivesTo evaluate the clinical efficacy and safety of TWG in the treatment of IMN.MethodsWe systematically searched PubMed, Embase, Cochrane Library, and Chinese databases from inception to September 2025. Randomized controlled trials (RCTs) and observational studies comparing TWG with standard therapies were included. Risk ratios (RR) and standardized mean differences (SMD) were pooled using a random-effects model.ResultsThis meta-analysis incorporated 20 studies (1,789 patients). TWG significantly improved the total response rate (RR = 1.27; 95% confidence interval (CI): 1.12–1.44), complete remission rate (RR = 1.81; 95% CI: 1.13–2.90), and reduced 24-h urinary protein (SMD = −2.09; 95% CI: 3.46 to −0.71) and recurrence risk (RR = 0.56; 95% CI: 0.37–0.86). However, the evidence was characterized by high heterogeneity (I2 > 50% for most efficacy outcomes) and a high risk of bias in 17 of the 20 included studies. No significant difference was observed in serum albumin (SMD = 1.20; 95% CI: 0.25–2.64) or the overall incidence of inadequately reported adverse events (RR = 0.93; 95% CI: 0.65–1.34).ConclusionTWG may represent a beneficial therapeutic strategy for IMN, potentially improving remission rates and reducing proteinuria. However, the conclusiveness of these findings is constrained by the high risk of bias in the primary studies, substantial heterogeneity, and inadequate safety reporting. Future robust, multi-regional RCTs are required to definitively establish its efficacy and safety profile.